Enhancement of impact toughness using graphene oxide in epoxy composite reinforced with ramie fabric. (15th February 2022) - Pereira, Artur Camposo; Monteiro, Sergio Neves; Simonassi, Noan Tonini; Vieira, Carlos Mauricio Fontes; Lima, Andreza Menezes; Costa, Ulisses Oliveira; Pinheiro, Wagner Anacleto; Oliveira, Michelle Souza; da Silva Figueiredo, André Ben-Hur
Abstract: The incorporation of graphene oxide (GO) in the polymeric composite reinforced with ramie fabric obtained an increase in impact and ballistic resistance. The investigation was divided into two lines: (I) of 0.2 vol% GO-incorporated in the epoxy resin; (II) and different GO (0.2 vol%) solutions that immersed the ramie fabric (30 vol%), with solutions based on water and isopropyl alcohol (IPA). The tests carried out were the Izod impact and the residual velocity tests carried out with a ballistic projectile. Scanning electron microscope (SEM) images of the fracture surface were obtained. The Izod impact values improved by 21.0 % when added 0.2 vol% of GO. For the GO solutions applied to the ramie fabric, there was no significant difference in the results. The use of the IPA solution in the ramie fabric resulted in the non-perforation of the projectile. The same was observed in the application of 0.2 vol% of GO in the epoxy, showing that a higher percentage may even result in better impact values and/or absorbed energy. However, such a configuration allows to maintain the integrity of the material after the ballistic impact.